Pintar! Child Development Centre (Pintar! ) / Ahmad Danial Zainudin ... [et.al.]. - Zainudin, Ahmad Danial; Anyi, Shera; Roselee, Nurul Nabila; Topek, Nur Atiqah; David Sating, Agnes (2010)
After a few discussions and meetings, a group of consisting five (5) ambitious people were agreed to form a name of this honorable organization to be stated as Pintar! Child Development Centre or it also simply being abbreviated as Pintar! CDC. But as the requirement from Sarawak State Welfare Department, any words followed after the name of the organization must be named as Taman Asuhan Kanak-kanak or TASKA. TASKA then translated into English language and brought the name as Pintar! Child Development Centre. The name itself already put up an imaginary among the public and community around to perceive the good image of organization and the pupils itself. The commencement date is mutually agreed to be held on 1st December 2010 at the Pintar! CDC where strategically located at the premise of No.4, Taman Murni, Jalan Akalifa, 93050 Kuching, Sarawak.